AGE Supplementation Modulates IL-6, IL-10 and HSP27 Response in Healthy Men - Paksoy, Serpil; Punduk, Zekine (Progress in Nutrition, 2022)
Abstract.  Background: Aged garlic extract (AGE) is a dietary supplement reported to have health benefits such as protection against oxidative stress, inflammatory disorders, and dyslipidemia. Methods: In this study the effects of AGE on the serum levels of interleukin-6 (IL-6), interleukin-10 (IL-10), heat shock protein 27 (HSP27), testosterone, cortisol, total antioxidant status (TAS), and total oxidant status (TOS) in healthy subjects was investigated.  Sedentary healthy men (n=6) participated in this study and ingested AGE (5 ml) for 10 days. During the study blood samples were taken in the morning before and 10 days after AGE supplementation, followed by another sample 10 days post-supplementation (wash out) period. The serum was analysed for biochemical parameters IL-6, IL-10, HSP27, cortisol, testosterone, TAS and TOS. These parameters were evaluated at the beginning of the study, end of AGE supplementation and at the end of the washout period. Conclusion: AGE supplementation caused an increase in the serum levels of the IL-6, IL-10 and HSP27 response and may have an important biological function in protection against oxidative stress and apoptosis by upregulating the levels of these parameters.